2023
DOI: 10.1111/vop.13065
|View full text |Cite
|
Sign up to set email alerts
|

Precorneal retention time of ocular lubricants measured with fluorophotometry in healthy dogs

Abstract: Objective: Determine the precorneal retention time of five different ocular lubricants commonly used in dogs.Animals Studied: Six healthy Beagle dogs (n = 12 eyes).Procedures: Five ocular lubricants were studied: Artificial Tears Solution® (1.4% polyvinyl alcohol), I-Drop® Vet Plus (0.25% hyaluronate), Optixcare® Eye Lube Plus (0.25% hyaluronate), Systane® Ultra (0.4% polyethylene glycol 400 and 0.3% propylene glycol), and Artificial Tears Ointment® (mineral oil/white petrolatum).Each lubricant was mixed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…One limitation of the trial is the possible influence of the product application on the STT values. In a recent article [ 10 ], published after the completion of our trial, the authors found that the precorneal retention time of 5 ocular lubricants ranged between 10 and 90 min, substantiating that the 2-h delay in the protocol could be relevant. A specific study to measure the residence time of the tested product would be of interest to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 55%
“…One limitation of the trial is the possible influence of the product application on the STT values. In a recent article [ 10 ], published after the completion of our trial, the authors found that the precorneal retention time of 5 ocular lubricants ranged between 10 and 90 min, substantiating that the 2-h delay in the protocol could be relevant. A specific study to measure the residence time of the tested product would be of interest to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 55%
“…Precorneal retention time was defined as the time (in min) that fluorescence of the tear film sample decreased below 5% of the baseline value. 9 Following the linear-log trapezoidal rule, the R software (version 3.6.0) was used to calculate the area under the concentration-time curves from 0 to 180 min (AUC 0-180 ) for each fluorescein concentration (0.3% or 1%) in the control experiment (single eye drop) and each of the five trials, that is, repeated eye drop administration at 30-s, 1-, 2-, 5-, and 10-min interval. The normality of the data was assessed with the Shapiro-Wilk test.…”
Section: Discussionmentioning
confidence: 99%